2017
DOI: 10.1097/aap.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Quadratus Lumborum Block Versus Transversus Abdominis Plane Block in Children Undergoing Low Abdominal Surgery

Abstract: The trial was registered prospectively at clinicaltrials.gov (NCT02715999).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 22 publications
5
97
1
2
Order By: Relevance
“…In the results of this study, they reported that they provided less morphine consumption and more prolonged analgesia in patients receiving QLB. In another study of a pediatric patient group, Öksüz et al found a decrease in the requirement for rescue analgesia after a posterior QLB block [23].…”
Section: Discussionmentioning
confidence: 93%
“…In the results of this study, they reported that they provided less morphine consumption and more prolonged analgesia in patients receiving QLB. In another study of a pediatric patient group, Öksüz et al found a decrease in the requirement for rescue analgesia after a posterior QLB block [23].…”
Section: Discussionmentioning
confidence: 93%
“…Although QLB has been found to be effective after inguinal hernia operation in the RCT results performed in pediatric patients, the discussions on the activity mechanism of the block have been addressed. One of the main activity mechanisms is blocking the sympathetic formations in the facial plane with local anesthetic, which has been suggested by Blanco et al (14). Another opinion is the paravertebral spread through the endothoracic fascia which is the continuation of the transversal fascia due to its anatomic structures (8).…”
Section: Discussionmentioning
confidence: 98%
“…Apart from the case reports in the literature, they have attempted to investigate the efficacy of QL block in three different studies (9,13,14). Murocchi et al have administered QLB and TAP blocks to 22 patients in two studies aiming to determine the efficacy of QLB after laparoscopic surgery in patients with gynecologic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The current study results also agreed with the findings of Öksüz et al, who compared QLB2 versus TAP blocks for postoperative pain relief in children undergoing lower abdominal surgery. Results of their study showed that the QLB2 provided longer and more effective postoperative analgesia, lower pain scores, and more parent satisfaction compared with TAP block [20].…”
Section: Resultsmentioning
confidence: 99%